Project-Based Learning, PPKn, pa “Penerapan Berbasis Project-Based Learning (PjBL) dalam Pembelajaran PPKn untuk Menumbuhkan Partisipasi Demokrasi pada Siswa SD: Tinjauan Literatur” - Nikita Aura Marshanda; Mira Amalia Amri; Adi Putra (Prodi Pendidikan Guru Sekolah Dasar, 2025)
Instilling democratic values from elementary school is a strategic step in shaping active and responsible citizens. The subject of Pancasila and Civics Education (PPKn) plays an important role in introducing democratic concepts. However, classroom learning is still dominated by lecture-style methods, which tend to make students passive. This study aims to analyze the application of the Project-Based Learning (PjBL) model in PPKn education to foster democratic participation among elementary school students. The research was conducted through a literature review of relevant national and international scientific articles. The results of the study indicate that PBL not only enhances students' understanding of democratic concepts but also develops collaboration, leadership, and decision-making skills. Through contextual projects, students are encouraged to actively participate, express their opinions, and engage in group decision-making processes. However, there are still few studies that specifically examine the relationship between PjBL and the development of democratic behavior among elementary school students. Therefore, further development is needed in the design of Civic Education (PPKn) learning that provides space for students to experience and practice democratic values directly. This study aims to provide guidance for teachers in developing learning activities that foster active student participation, contextual relevance, and meaningful learning experiences.